ANALISIS PEMANFAATAN MULTIMEDIA TERHADAP PENGUASAAN KONSEP REAKSI NUKLIR MAHASISWA PADA MATAKULIAH FISIKA INTI - Lailatul Nuraini; Bambang Supriadi (FKIP Universitas Jember, 2018)
One of the uses of multimedia is to explain abstract concepts that cannot be directly observed by the five senses to be more easily understood, especially related to the concept of nuclear reactions in nuclear physics courses. This research aimed to get an overview of the mastery of the concept of nuclear reactions in students who take core physics courses and get an overview of the responses of students' perceptions of learning. The method of this research was experimental research with one group pretest-posttest design. Data collection techniques used in this research include the mastery test, student response questionnaire, documentation and observation. Data analysis techniques include descriptive analysis of student response questionnaires about multimedia-assisted nuclear physics learning process and analysis of mastery test results of the concept of nuclear reactions in nuclear physics courses using Ngain scores. The results showed that there was an increase in mastery of the nuclear reaction concept in nuclear physics subject with score of n-gain result was 0.41 and came into medium category. The ability to master concepts includes the ability to remember, understand, apply, analyze and evaluate. Based on this description, it can be concluded that the use of multimedia can increase students’ mastery concepts of nuclear reactions concept in nuclear physics courses.